Reduced 24-h Sodium Excretion Is Associated With a Disturbed Plasma Acylcarnitine Profile in Vasovagal Syncope Children: A Pilot Study - Song, Jinqing; Tao, Chunyan; Chen, Guozhen; Chen, Selena; Xu, Wenrui; Du, Junbao; Yang, Yanling; Huang, Yaqian (Frontiers in Pediatrics, 2020)
Objective: To investigate if the low sodium intake is associated with the plasma carnitine and acylcarnitine profile in children with vasovagal syncope (VVS). Materials and Methods: Twenty-six children suffering from VVS were recruited in the present study and divided into a group of low urinary sodium excretion or a group of normal urinary sodium excretion according to the excretion of 24-h urinary sodium < 3 grams or 3-6 grams, respectively. The excretion of 24-h urinary sodium was detected with ion-selective electrode approach. Plasma carnitine and acylcarnitine concentrations were measured with tandem mass spectrometry. Each participant completed the head-up tilt test. The demographics, clinical characteristics, hemodynamic parameters and plasma carnitine and acylcarnitine concentrations were compared between the two groups. A bivariate correlation between plasma acylcarnitine profiles and the excretion of 24-h urinary sodium was conducted with Spearman’s correlation coefficients. Results: Of the enrolled VVS patients, 14 patients were assigned to the group of low urinary sodium excretion and the remaining 12 patients were assigned to the group of normal urinary sodium excretion. Symptoms of fatigue were more prevalent in the group of low urinary sodium excretion than in the group of normal urinary sodium excretion (p = 0.009). Aside from fatigue, no other differences in the demographics, clinical characteristics or hemodynamic parameters during the head-up tilt test were found between the two groups (p > 0.05). Concentrations of plasma tiglylcarnitine (C5:1), hydroxyhexadecanoylcarnitine (C16OH), hydroxyoctadecanoylcarnitine (C18OH) and carnitine C22 were significantly higher in the group of low urinary sodium excretion than in the group of normal urinary sodium excretion (all p values = 0.048); moreover, they were all negatively correlated with 24-h urinary sodium levels (all p values = 0.016). There were no differences between the two groups in other acylcarnitines or free carnitine. Conclusions: Reduced excretion of 24-h urinary sodium is associated with a disturbed plasma acylcarnitine profile in children with VVS. The findings suggest that restricted sodium intake-induced disturbance of plasma acylcarnitines and related cellular energy metabolism might be involved in the pathogenesis of VVS in children.